PEMBERIAN KIE PADA REMAJA TENTANG DAMPAK PERNIKAHAN USIA DINI PADA KESEHATAN REPRODUKSI - NUNUK NURHAYATI NUNUK NURHAYATI; Partina (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2022)
Adolescence is a transitional period marked by physical changes due to the maturation of adolescent reproductive organs, which is marked in women by the arrival of menstruation and in men by the ability to produce sperm or wet dreams. The incidence of early marriage is still very high, especially in Mojokerto Regency in 2022 because according to data from the Mojokerto Ministry of Religion, there was an application for an increase in the Age of Marriage dispensation at the Mojokerto KUA office. The age of marriage according to the Law of the Republic of Indonesia No. 16 of 2019, which is regarding the marriage law regarding the age limit for marriage is 19 years because at the age of 19 years it is considered to be able to do a good marriage and that age is considered to be able to obtain healthy offspring and psychological conditions as well as think it's ripe for marriage. Seeing the condition that there is still a large number of marriages at an early age, it is considered necessary and important for health education to provide health education to adolescents about the impact of early marriage on adolescent reproductive health. To overcome this problem, one of them is to implement preventive activities through the provision of IEC among adolescents, namely at the high school level regarding the health of the reproductive organs and the dangers of early marriage on the reproductive organs because early marriage causes maternal and infant mortality. This is because the reproductive organs are not well developed and pregnancy in adolescence is at risk for complications of pre-eclampsia/eclampsia and is at risk of bleeding. This community service is carried out for approximately 2 months, namely, the active planning process includes identifying needs, identifying potentials and weaknesses, and determining solutions to problems that have been determined. 2. Coordination activities: carried out by lecturers and teams by meeting the principal and the teacher council, then making an agreement on the design of activities that will be carried out for the implementation of community service 3. Active in the Implementation stage: Community service programs with the theme of Giving KIE to teenagers about the impact of age marriage and Early childhood education on reproductive health will be held on June 17, 2022, at 09.00 WIB at MA Al Masyudi Mojokerto. With the support of all parties, this community service activity runs smoothly and orderly and PIK-R activities in schools should be revived and increase cross-sectoral collaboration with local community health centers.